2021
DOI: 10.1186/s13019-021-01485-z
|View full text |Cite
|
Sign up to set email alerts
|

Low suction on digital drainage devices promptly improves post-operative air leaks following lung resection operations: a retrospective study

Abstract: Background We investigated the most effective suction pressure for preventing or promptly improving postoperative air leaks on digital drainage devices after lung resection. Methods We retrospectively analyzed the postoperative data of 242 patients who were monitored with a digital drainage system after pulmonary resection in our institution between December 2017 and June 2020. We divided the patients into three groups according to the suction pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For this reason, most of literature is about postoperative PAL conservative management, that can rely on fewer options than intraoperative air leak treatment. To date, in case of completely expansible residual lung parenchyma, PAL treatment may be safely attempted by autologous blood patch or chemical pleurodesis (37)(38)(39)(40)(41)(42), whereas in case of residual pleural space, applying suction to the chest drain is still the most effective option available (43)(44)(45)(46)(47)(48). In all cases, digital drainage systems are useful since they allow early patients' mobilization and a real time quantification of air flow (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, most of literature is about postoperative PAL conservative management, that can rely on fewer options than intraoperative air leak treatment. To date, in case of completely expansible residual lung parenchyma, PAL treatment may be safely attempted by autologous blood patch or chemical pleurodesis (37)(38)(39)(40)(41)(42), whereas in case of residual pleural space, applying suction to the chest drain is still the most effective option available (43)(44)(45)(46)(47)(48). In all cases, digital drainage systems are useful since they allow early patients' mobilization and a real time quantification of air flow (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Alphonso et al in their paper written in 2005 (44) declared to be in favor of a no-suction policy, while Holbek et al, in their randomized controlled trial of 2018 (47) compared water seal to a low suction (−10 cmH 2 O), encountering a significantly shorter chest drain duration in the second group. Finally, Mitsui and coauthors highlighted, in their retrospective report of 2021 (48), as a low-pressure suction (−10 cmH 2 O) promptly improve postoperative air leaks if compared to lower negative pressures (−20 cmH 2 O).…”
Section: Postoperative Pal Conservative Managementmentioning
confidence: 99%
“…Lower pressures within this range are recommended for pediatric patients and can potentially improve outcomes following lung resections in people. [1][2][3]7 Suction pressures up to 40 cm H 2 O may be required for viscous fluid drainage. 2 The suction pressure of the proposed designs is limited by the length of the straw and depth of the canister.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended initial pressures for pleural suction are generally between 5 and 20 cm H 2 O. Lower pressures within this range are recommended for pediatric patients and can potentially improve outcomes following lung resections in people 1–3,7 . Suction pressures up to 40 cm H 2 O may be required for viscous fluid drainage 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations, including a randomized controlled trial published by Holbek et al, revealed that low suction (−10 cm H 2 O) notably decreased the duration of chest drainage in comparison to water seal [35]. Additionally, retrospective analyses reported by Mitsui et al have suggested that a low-pressure suction (−10 cm H 2 O) is more effective at improving postoperative air leaks than lower negative pressures (−20 cm H 2 O) [36]. These divergent findings highlight the ongoing debate and need for conclusive research to establish standardized guidelines for chest drain management following thoracic surgery to minimize air leak durations [2,15].…”
Section: Chest Tube Managementmentioning
confidence: 99%